EVALUASI MATERI PENDIDIKAN ISLAM PERSPEKTIF GENDER - Jumni Nelli (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2011)
Education is a tool for transferring the norms of society, knowledge and human capabilities, as well as a tool to assess and convey ideas and new values, including values and norms of gender. Know to have been a lot of gender inquality in society wich is assumed to arise because there is a gender bias in education. Including religious education. As an example of gender bias in te curriculum of the Islamic religion including the material about the origin of human events, the obligation to pray in congregation, the provisions of polygamy, the fungtions of husband and wife in munakahat. In an effort to realize the nature of religious understanding of gender, it is appropriate necessary revisions to matters of gender bias in text books Islamic Religion. It should be all parties, especially the author and editor of books on the fact that the existing curriculum is not gender neutral. Meanwhile, for teachers of religion claimed to be mor critical and sensitive in the review and examine all matters realting to gender ineguality in the learning process taking place in ther daily work